Droplet aerosol dissemination of carbapenem-resistant Acinetobacter baumannii surrounding ventilated patients. (18th February 2019) - Mousa, Madelyn; Schwartz, David; Carmeli, Yehuda; Nutman, Amir
Abstract: We measured droplet aerosol dissemination of carbapenem-resistant Acinetobacter baumannii (CRAB) by sampling air surrounding 10 ventilated patients with CRAB isolated in sputum. Over 70 hours, we sampled 252, 000 L of air; CRAB was detected in 39, 600 L (16%). CRAB growth was higher during patient care, notably suctioning and sheet changing.